Exploring the Impact of Implementing Building Information Modelling to Support Sustainable Development in the Lebanese Construction Industry: A Qualitative Approach - Shibani, Dr Abdussalam; Michal Ghostin; Dyaa Hassan; Messaoud Saidani; Araz agha (IJRDO - Journal of Mechanical And Civil Engineering, 2021)
Building Information Modelling has been identified as a new and revolutionary tool capable of improving the performance of the construction sector. With a growing population and overurbanization, there is an increasing demand for construction projects in Lebanon, thus hindering the environment and consuming natural resources. The Lebanese construction sector has been neglecting the importance of sustainable development; however, this research adopts a qualitative approach to explore the influence of implementing Building Information Modelling in the Lebanese construction industry to support sustainable development. The aim of this research is to develop a framework for the successful implementation of BIM by examining the barriers limiting BIM implementation in terms of economic, social, and environmental sustainability also referred to as sustainability pillar. Interviews were carried out with construction professionals in Lebanon to understand the definition, benefits, barriers, and current sustainable performance to further examine the implementation of BIM. The framework is divided into seven components that will unlock the possibility of implementing BIM in the Lebanese construction industry to achieve sustainable growth.